2021
DOI: 10.1021/jacs.1c03923
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Asymmetric Multicomponent Cascade Reaction for the Synthesis of Contiguously Substituted Tetrahydronaphthols

Abstract: Isobenzopyrylium ions are unique, highly reactive, aromatic intermediates which are largely unexplored in asymmetric catalysis despite their high potential synthetic utility. In this study, an organocatalytic asymmetric multicomponent cascade via dienamine catalysis, involving a cycloaddition, a nucleophilic addition, and a ring-opening reaction, is disclosed. The reaction furnishes chiral tetrahydronaphthols containing four contiguous stereocenters in good to high yield, high diastereoselectivity (up to >20:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 79 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…We would like to comment on a pivotal recent example, since sometimes it is difficult to separate a multicomponent reaction from a cascade process, and the complexity of both processes together can be of extraordinary elegance [73]. Recently, Jørgensen and co-workers reported an amazing example of an organocatalytic multicomponent cascade process via dienamine catalysis, involving at the same time a cycloaddition, a nucleophilic addition, and a ring-opening reaction between uncommon isobenzopyrylium precursors, α,β-unsaturated aldehydes, and H 2 O [74]. The process was successfully developed to prepare chiral tetrahydronaphthols containing four contiguous stereocenters in good to high yield (up to 95%), high diastereoselectivity (up to >20:1), and excellent enantioselectivity (93−98% ee) (Scheme 4).…”
Section: Organocatalytic Asymmetric Multicomponent Reactionsmentioning
confidence: 99%
“…We would like to comment on a pivotal recent example, since sometimes it is difficult to separate a multicomponent reaction from a cascade process, and the complexity of both processes together can be of extraordinary elegance [73]. Recently, Jørgensen and co-workers reported an amazing example of an organocatalytic multicomponent cascade process via dienamine catalysis, involving at the same time a cycloaddition, a nucleophilic addition, and a ring-opening reaction between uncommon isobenzopyrylium precursors, α,β-unsaturated aldehydes, and H 2 O [74]. The process was successfully developed to prepare chiral tetrahydronaphthols containing four contiguous stereocenters in good to high yield (up to 95%), high diastereoselectivity (up to >20:1), and excellent enantioselectivity (93−98% ee) (Scheme 4).…”
Section: Organocatalytic Asymmetric Multicomponent Reactionsmentioning
confidence: 99%
“…These intriguing transformations are initiated by concerted [5 + 4]- or [4 + 2]-cycloadditions of vinyl diazo compounds with gold complex-stabilized isobenzopyrylium intermediates, followed by ring opening and rearrangement. Instead of gold catalysis with ortho-alkynylbenzaldehydes, we surmised that the reaction of 1 H -isochromene acetal with Brønsted acid catalysts would give ionic isobenzopyrylium salts that could also undergo vinylogous addition to vinyl diazo compounds with overall [4 + 3]-cycloaddition like that of Scheme b through vinyl diazonium and vinyl carbocation intermediates. Instead, we discovered a metathesis transformation that forms tunable rearranged products in high yields and diastereoselectivities.…”
Section: Introductionmentioning
confidence: 99%
“…Multicomponent reactions (MCRs) have the advantages of simpler procedures, atom economy and product complexity. They have attracted increasing interest in synthetic, [17][18][19] materials 20 and pharmaceutical chemistry. [21][22][23] In recent years, we have focused on the development of efficient MCRs for the synthesis of novel heterocycles [24][25][26][27][28][29] as well as their bioactivities, [30][31][32][33] optical properties and applications.…”
mentioning
confidence: 99%
“…3 ) (entries 14 and 15) but increased by the addition of Brønsted acids, such as hydrochloric acid (HCl), sulfuric acid (H 2 SO 4 ), trifluoroacetic acid (TFA) and acetic acid (AcOH) (entries[16][17][18][19], with H 2 SO 4 being the best one (entry 17) which caused the yield of 4a to increase to 51%. The screening of the amount of H 2 SO 4 (entries 17, 20-21) indicated that 0.5 equivalent of H 2 SO 4 is suitable (entry 17).…”
mentioning
confidence: 99%